Judo Sport Regulations for Children's Parents in The Pre-School Children Judo Education: Study of Field - Sengul Demıral (Selcuk University, 2018)
The fact that children have been acquainted with sports from their early years is an important determinant of their attitudes and behaviors in their future lives and constitutes the most basic part of a country's athletic resource in broadcast sports policies. Early childhood is important in supporting the development of children as well as in acquiring certain habits. Quality management of this time zone is also important. For this reason, in this research, it was aimed to examine the opinions and expectations of the parents of preschool children who are in pre-school education to direct their children to judo sports. The data are arranged in categories, interpreted as descriptive and frequency. As a result, according to priority order; it is important for the female parents that their children are healthy, develop their own discipline, learn sports culture and morality. Moreover, they want them to be psychologically good and healthy as well as expecting them to socialize, learn sports culture and morality, develop their self- discipline. Also, they are guiding their children to judo sports because they want to improve morality, social cohesion and self-discipline. The results obtained in Turkey Judo Federation and judo policies will be developed in preschool education for coaches, and will create significant resources and proposals for the strategy which has been developed for data.